2001
DOI: 10.1007/s007050170146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fatty acids on arenavirus replication: inhibition of virus production by lauric acid

Abstract: To study the functional involvement of cellular membrane properties on arenavirus infection, saturated fatty acids of variable chain length (C10-C18) were evaluated for their inhibitory activity against the multiplication of Junin virus (JUNV). The most active inhibitor was lauric acid (C12), which reduced virus yields of several attenuated and pathogenic strains of JUNV in a dose dependent manner, without affecting cell viability. Fatty acids with shorter or longer chain length had a reduced or negligible ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 28 publications
0
32
0
1
Order By: Relevance
“…[30][31][32] VCO and several of its constituent fatty acids: lauric, capric, and caprylic acid have been shown in other studies to inhibit the growth of microbes, including enveloped viruses, yeast (e.g., C. albicans), and bacteria (e.g., C. perfringens). 11,12,[14][15][16]18,23,33 VCO, when consumed, would be digested by lipases of the digestive tract, releasing the individual fatty acids and ultimately inhibiting the growth of microorganisms in vivo. 34 C. difficile lacks lipases to digest coconut oil, 35,36 requiring the oil to be lipolyzed with porcine lipase before evaluating its effect in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] VCO and several of its constituent fatty acids: lauric, capric, and caprylic acid have been shown in other studies to inhibit the growth of microbes, including enveloped viruses, yeast (e.g., C. albicans), and bacteria (e.g., C. perfringens). 11,12,[14][15][16]18,23,33 VCO, when consumed, would be digested by lipases of the digestive tract, releasing the individual fatty acids and ultimately inhibiting the growth of microorganisms in vivo. 34 C. difficile lacks lipases to digest coconut oil, 35,36 requiring the oil to be lipolyzed with porcine lipase before evaluating its effect in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several natural and synthetic products have been reported as active in vitro inhibitors against arenavirus infection. The compounds under study include steroids (Wachsman et al, 2000), polysulfates (Andrei & De Clercq, 1990;Witvrouw et al, 1994), thiosemicarbazones (García et al, 2003a), trichothecenes (García et al, 2002b), phenothiazines (Candurra et al, 1996), fatty acids and analogues (Cordo et al, 1999;Bartolotta et al, 2001) and peptides (Castilla et al, 1998;Albiol Matanic & Castilla, 2004). Recent research on antiviral strategies against LCMV also describes the potential application of certain nucleoside analogues for increased mutagenesis (Grande-Pérez et al, 2005), as well as the downregulation of gene expression produced by small interfering RNAs (Sánchez et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…To date, few studies have investigated the apoptotic properties of lauric acid. However, published literature has reported that lauric acid exerts antimicrobial effects by inhibiting growth or reducing cell viability in bacterial and viral species [36,37,38]. …”
Section: Discussionmentioning
confidence: 99%